Phacoemulsification versus extracapsular cataract extraction: a comparative study of cell survival and growth on the human capsular bag in vitro. Issue 10 (1st October 1997) - Quinlan, M; Wormstone, I M; Duncan, G; Davies, P D
Abstract : AIMS/BACKGROUND: Phacoemulsification is rapidly replacing conventional extracapsular cataract extraction (ECCE) as the method of choice for cataract surgery in the Western world. However, posterior capsule opacification (PCO) still remains the major postoperative complication, affecting 20–50% of patients, and results from persistent cell growth of epithelial cells remaining after surgery. This study aimed to compare cell survival and growth on capsular bags following ECCE and phacoemulsification surgery using an established human capsular bag culture system. METHODS: Sham ECCE and phacoemulsification cataract operations were performed on pairs of human donor eyes. Capsular bags were dissected free, pinned flat on a petri dish, and incubated with Eagle's minimum essential medium (EMEM) alone or EMEM supplemented with 10% fetal calf serum (FCS). Ongoing observations were made using phase contrast microscopy. RESULTS: Cell growth was observed across the posterior capsule of all preparations studied. It was found that there was no significant difference in the rate of cell growth on the posterior capsule with the two extraction methods, such that 50% confluency was achieved in 7.0 (SD 1.8) (n=7) days for ECCE and 7.43 (2.1) (n=7) days for phacoemulsification surgery. The physical changes to the capsule as a result of cell growth, such as wrinkling and capsular tensioning, were also seen in both groups. CONCLUSIONS: Cell survival and growth is dependent on the donor, rather than the surgical technique performed. There is no significant difference between phacoemulsification and ECCE surgery on the rate and nature of cell growth on the posterior capsule in vitro.